The mechanism of NFKB signalling in odontogenic stem cell differentiation induced by bmp2 for dental pulp tissue engineering - Ahmad, Azlina (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2019)
NF-KB signalling pathway is involved in the tooth organogenesis and eruption process, With the elimination of NF-KB pathway could lead to a developmental detention of teeth. Hence, this study was conducted to investigate the mechanism of NF-KB signalling in the differentiation of SHED into odontoblast-like cells. Analysis of NF- KB signalling was divided into two phases. The first phase was aimed to identify the optimal concentration of inhibitors, The second phase of the study was aimed to investigate the expression of stem cell, odontogenic, and NF-KB gene markers. Further analyses were carried out using real time RTPCR. In conclusion, based on the gene expression analysis, this study suggested that inhibition of NF-KB directly involves in odontogenic differentiation of SHED when cultured on HAM with the treatment of BMP-2.